Wymiary kultury a grzeczność w języku - Zięba, Anna (Investigationes Linguisticae, 2010)
This article dwells on the relationship between expressions of politeness such as forms of address, greetings and parting phrases, apologies, advice, curses, etc. and cultural differences presented within the framework of Geert Hofstede’s 5D model. The author discusses the impact that culture has on politeness in language and proves her point by giving examples of the influence of individualism and collectivism, power distance, femininity and masculinity as well as uncertainty avoidance on the way politeness is expressed in different cultures. Also the relationship between the usage of plural and singular form is studied.